Sosialisasi Pengembangan Desain Produk Baru Kerajinan Akrilik - Nanang Fatchurrohman; Mutiara Yetrina; Mohammad Farid (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
The initial survey has been conducted by our team in the Acrylic Craft Thematic Village Gunung Pangilun, Padang City, which we abbreviate as â€œKampung Akrilikâ€. From interviews with local artisans, our team realized that the marketing of SME products in this village has not been fully optimized, primarily due to a lack of product variety offered. Faced with this issue, our team felt challenged to contribute by helping direct the artisans to focus on developing products that align with the needs and preferences of potential buyers. Furthermore, we also identified the necessary raw materials and equipment required to create the previously identified new products. Once the new products were identified, the next step was to organize a socialization event. This socialization includes the techniques for creating the new products, such as 3D printing. Through this Community Service project, we hope to revitalize productivity in Acrylic Village. We aim to assist the local community in increasing their product sales and achieving an overall improvement in sales volume.